THE ORTHODOX RELIGIOUS PUBLICATIONS IN ROMANIA FROM THE CLASSICAL PRINTING TO ONLINE EDITIONS - DASCĂLU, Nicolae (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
A research on the rise and decline of the Romanian Orthodox religious media in the last 30 years cannot ignore the paradigm shifts caused by the emergence of new information and communication technologies and the global Internet network. The theological and spiritual contents do not instantly adapt to technological innovations and, therefore, the printing press remains a space for reflection in religious communication, between the opportunities and risks of rapid change. The transition of religious publications from print editions to online editions is necessary. However, by virtue of spiritual discernment, it requires a balance between tradition and renewal. This balance is kept due to three elements: the respect for the heritage of the printed sacred culture, the pastoral care for the older generations and the awareness of the responsibility for the unaltered transmission of the spiritual content of faith to the generation of digital natives.